2015
DOI: 10.1007/s40415-015-0179-1
|View full text |Cite
|
Sign up to set email alerts
|

Harvest times of Comanthera elegans, a worldwide traded Brazilian species of everlasting flower: implications on seed production, germination, and on species management

Abstract: Comanthera elegans (Bong.) L.R. Parra & Giul (''sempre-viva-pé-de-ouro'') is one of the most economically important species among the Eriocaulaceae in Brazil. Its inflorescences are used to make handicrafts and have long been exported to all over the world. The collection period usually begins in the second half of April and extends to May, occasionally until the first half of June. We assessed seed production and germinability throughout the 2006 harvest season: April-November, as well as the variation in mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…For the results of the tetrazolium test at the end of the germination test, it was observed that the remaining seeds were not viable (Table 1). Similar results regarding the low percentage of germination in everlasting seeds were found in the work of Garcia et al 2014; Oliveira et al (2015). These low germination results are expected since many authors have highlighted some aspects such as: climate variation that can influence the beginning and end of the harvest, the physiological state in which the seed is, the period of maturation or could be by climatic conditions and/or edaphic micro conditions of the place in where the plants developed in which seeds were produced (Oliveira & Garcia, 2011).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…For the results of the tetrazolium test at the end of the germination test, it was observed that the remaining seeds were not viable (Table 1). Similar results regarding the low percentage of germination in everlasting seeds were found in the work of Garcia et al 2014; Oliveira et al (2015). These low germination results are expected since many authors have highlighted some aspects such as: climate variation that can influence the beginning and end of the harvest, the physiological state in which the seed is, the period of maturation or could be by climatic conditions and/or edaphic micro conditions of the place in where the plants developed in which seeds were produced (Oliveira & Garcia, 2011).…”
Section: Resultssupporting
confidence: 88%
“…Several authors have observed low physiological quality in everlasting seeds. Oliveira et al (2015) affirm that the highest rate of germination of C. elegans, at a temperature of 25±2 °C, was 22.932% for seeds collected in the month of September. In the collections in the periods that precede or follow this month, the percentage of germination did not surpass 11.72%.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Recruiting through seeds is commonly observed in Eriocaulaceae species (CASTELANI, 1996;SANO, 1996), including those in the genera Comanthera (OLIVEIRA et al, 2014;OLIVEIRA et al, 2015) and Syngonanthus (SCHMIDT et al, 2007). For Syngonanthus nitens (golden grass), 40% of the plants in a population evaluated by Schmidt et al (2007) were recruited via seeds.…”
Section: Discussionmentioning
confidence: 99%
“…The scapes, with the capitula and flowers, when detached from the rest of the plant, continue to appear living, from which the popular names of "everlasting plants", or in Brazil "sempre-vivas", originate. Because of their beauty, the scapes and capitula are collected and sold as decoration in the house, and has resulted in an intensive extractive industry (Giulietti et al , 1996Oliveira et al 2015).…”
Section: Introductionmentioning
confidence: 99%